Bacillus circulans xylanase: Stability and mechanism of action. - Davoodi, Jamshid. (University of Ottawa (Canada), 1996)
The stability and mechanism of the action of the enzyme Bacillus circulans xylanase (1,4-$\beta$-D-xylanohydrolase, EC 3.2.1.8) were investigated by various biophysical techniques. On the basis of the sequence homology between B. circulans xylanase and xylanase A from Schizophyllum commune, a disulphide bond was introduced between the residues 100 and 148, S100C/N148C (DS1 mutant). The presence of this covalent cross-link leads to a 5$\sp\circ$C increase in the melting point of the protein, as verified by differential scanning calorimetry. Introduction of another disulphide bond in a similar position, V98C/A152C, the DS2 mutant also enhances the stability of the protein by as much as 4$\sp\circ$C. On the basis of the notion that the increase in the stability of a protein is proportional to the number of residues encompassed by the cross-link, the N and C-termini were joined, A1GC/G187,C188, to form the circular xylanase (cXI) mutant. This mutant also acquired a 3.8$\sp\circ$C elevated melting point. A combination of S100C/N148C and A1GC/G187,C188 mutations is accompanied by a 12.3$\sp\circ$C increase in the melting point, which is 3.5$\sp\circ$C more than expected. Thus, the stabilization effect of the two disulphide bonds appears to be cooperative rather than additive. Moreover, the thermodynamic data obtained from differential scanning calorimetry under reversible conditions support previous findings that the stabilizing effect of disulphide bonds is a consequence of a decreased conformational entropy of the unfolded state. Furthermore, the results of this study support the notion that the introduction of a disulphide bond can be used as a strategy to prevent the aggregation of proteins by restricting the exposure of some elements required for this process. The active site of Bacillus circulans xylanase contains two acidic residues, glutamic acids 78 and 172, which are crucial for the catalytic activity of the enzyme. Fourier-transform infrared and near-UV circular dichroism spectroscopies were used to determine the pK$\rm\sb{a}$ of these residues. For the wild type enzyme, a titration of one of carboxylate groups occurs at pH 6.8, as evidenced by FT-IR spectroscopy. This titration is absent in the E78Q of E172Q variants of the enzyme. This, taken with crystallographic data, indicates that glutamic acid at position 172 has an abnormally high pK$\rm\sb{a}$ of 6.8. The high pK$\rm\sb{a}$ value of Glu 172 is caused largely by electrostatic interactions of this residue with a proximal glutamic acid at position 78. Furthermore, the circular dichroism spectrum of the wild type xylanase shows a structural transition at pH 4.9 in the near-UV region which is absent for the E78C mutant. This taken with the fact that glutamic acid 78 forms a network of hydrogen bonds with tyrosine 69 and tryptophan 71 indicates that the transition with pK$\rm\sb{a}$ 4.9 should be attributed to glutamic acid 78. The presence of two proximal carboxyl groups, from glutamic acids 78 and 172, results in a pH-dependent destabilisation of the protein structure as evidenced by differential scanning calorimetry experiments, with the wild type xylanase and a number of mutant proteins.
Keywords: Biology, Microbiology.